Using a confined space to boost the driving amplitude of pulsating bubbles to facilitate jetting - Carlson Craig S.; Anderton Nicole; Aharonson Vered; Otake Naoyuki; Xinyue Hu; Yamasaku Momoka; Hashimoto Mamoru; Kudo Nobuki; Postema Michiel (Current Directions in Biomedical Engineering)
A bubble collapsing near an interface may result in the formation of a liquid jet protruding from the distal bubble side, through the bubble, towards the interface. Ultrasound assisted jetting has been observed when subjecting, by approximation, infinite fluids to acoustic amplitudes above the inertial cavitation threshold, limiting the possibility of ultrasoundguided, bubble-assisted drug or gene delivery. However, the vascular system can be regarded as a finite fluid. The purpose of this study was to investigate the feasibility of lowamplitude jetting for fluid containing biocompatible cavitation nuclei, by placing the region of interest in a confined space to ensure a standing wave field. Droplets of QuantisonTMultrasound contrast agent were pipetted into a Perspex cylindrical compartment of 8-mm diameter and 2-mm height, which was part of an imaging system. The contrast agent was subjected to 3-cycle ultrasound pulses with a centre frequency of 1MHz whilst being observed at a frame rate of ten million frames per second. Jetting was observed to occur with microbubbles nucleated from the contrast agent in an acoustic regime whose free-field mechanical index was 0.6. Empirical curve matching showed a pulse amplification by a factor of six owing to the chosen geometry. Visible jet lengths of twice the bubble radius on the verge of collapse were measured. Owing to the confined space, the local acoustic amplitude was amplified to surpass the cavitation threshold. This finding is of interest for medical ultrasonic applications where the local environment comprises reflectors.